Rancang Bangun Aplikasi Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada UPT. PPPK Dinas Pendidikan Jawa Timur - Ika Sustianing Ifani; Sulistiowati Sulistiowati; Yoppy Mirza Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2015)
In East Java, the unit technical of operational and the development of vocational education (UPT.PPPK) have work such as train, development of vocational education, administration and community service. The quality implementation of vocational education does vocational training for students, teachers and community education. During improvement of training, UPT.PPPK do the procedure of measurement of customer satisfaction. It is useful for process analysis of customer satisfaction but there are some problems that are filling up the questionnaire of customer satisfaction manually, one of the content of questionnaire of customer satisfaction is static of questionnaire variable so that it does not produce a complex variable services, the process and analysis of questionnaire manually which use Microsoft Excel so that there are delay of making the report and follow-up the process of improvement services. Based on that problem, it requires an application for analysis the measurement of customer satisfaction. The application would uses a method measurement service quality and multiple linear regressions. By using the application, it reduces the risk of analyzing the data of measurement of customer satisfaction and achieves customer satisfaction